Prevalence of Low Cardiovascular Risk Profile Among Diverse Hispanic/Latino Adults in the United States by Age, Sex, and Level of Acculturation: The Hispanic Community Health Study/Study of Latinos. Issue 8 (August 2016) - Daviglus, Martha L.; Pirzada, Amber; Durazo‐Arvizu, Ramon; Chen, Jinsong; Allison, Matthew; Avilés‐Santa, Larissa; Cai, Jianwen; González, Hector M.; Kaplan, Robert C.; Schneiderman, Neil; Sorlie, Paul D.; Talavera, Gregory A.; et al.
Abstract : Background: Favorable levels of all readily measurable major cardiovascular disease risk factors (ie, low risk [LR]) are associated with lower risks of cardiovascular disease morbidity and mortality. Data are not available on LR prevalence among Hispanic/Latino adults of diverse ethnic backgrounds. This study aimed to describe the prevalence of a low cardiovascular disease risk profile among Hispanic/Latino adults in the United States and to examine cross‐sectional associations of LR with measures of acculturation. Methods and Results: The multicenter, prospective, population‐based Hispanic Community Health Study/Study of Latinos examined 16 415 men and women aged 18 to 74 years at baseline (2008–2011) with diverse Hispanic/Latino backgrounds. Analyses involved 14 757 adults (mean age 41.3 years; 60.6% women). LR was defined using national guidelines for favorable levels of serum cholesterol, blood pressure, and body mass index and by not having diabetes mellitus and not currently smoking. Age‐adjusted LR prevalence was low (8.4% overall; 5.1% for men, 11.2% for women) and varied by background (4.2% in men of Mexican heritage versus 15.0% in women of Cuban heritage). Lower acculturation (assessed using proxy measures) was significantly associated with higher odds of a LR profile among women only: Age‐adjusted odds ratios of having LR were 1.64 (95% CI 1.24–2.17) for foreign‐born versus US‐born women and 1.96 (95% CI 1.49–2.58) for women residing in the United States <10 versus ≥10 years. Conclusions: Among diverse US Hispanic/Latino adults, the prevalence of a LR profile is low. Lower acculturation is associated with higher odds of a LR profile among women but not men. Comprehensive public health strategies are needed to improve the cardiovascular health of US Hispanic/Latino adults.